COVID-19: A SYSTEMATIC REVIEW OF IMPLICATIONS FOR TRADE COMPETITIVENESS - Sharul Shahida Shakrein Safian; Norashida Othman; Nur Azirah Zahida Mohamad Azhar; Siti Norida Wahab (International Journal of Accounting, Finance and Business, 2021)
Trade is essential to keep supply chains flowing, especially for essentialsproducts during the unprecedented global spread of the novel coronavirus diseas e 2019(also known as the COVID-19 pandemic). Since the beginning of the pandemic, scholarshave been studying and publishing research on various trade competitiveness issues.However, although the number of papers on this topic has gradually increased, it remainsuncertain on what aspects of this disruption have already been examined and what aspectsstill need to be explored because of the absence of any systematic reviews of literature.The method of systematic literature review (SLR) is adapted to systematically review theexisting research on the COVID-19 pandemic in trade disciplines. To carry out thissystematic review, the PRISMA (Preferred Reporting Items for Systematic reviews andMeta-Analyses) review method has been utilized to attain an organized and adequatestructure of the manuscript. Two leading bibliography databases namely Scopus and Webof Science have been searched using â€œCOVID-19â€ and â€œTrade Competitivenessâ€ askeywords. Through a rigorous and systematic search, this study reveals the methodologies,background, and ideas used in each research alongside the synthesis of the results. Thisstudy offers research directions for further analysis by combining the findings of thesestudies. These guidelines will help researchers in the design and conducted impactfulresearch focusing on export competitiveness.